Musical Literacy - Planinc, Luka (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter explores the theoretical foundations of music literacy and its significance. It introduces the concept of music literacy and outlines how it should be implemented to achieve positive outcomes for pupils and individuals. The chapter also examines the importance of developing musical listening skills, highlighting how these contribute to enhanced musical literacy. Additionally, it discusses the broader benefits of fostering musical literacy, not only from an educational perspective but also in terms of its impact on an individual’s overall development.